Marriage Contract Through Teleconference During the Covid-19 Pandemic: An Overview of Maqashid Syariah - Supriadi Supriadi (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri Bone, 2021)
Rapid technological developments have affected all aspects of people's social life, including in the field of marriage. One indication is the use of teleconference developments as a medium for conducting marriage contracts, but the problem is, Islamic law has not specifically regulated the rules or laws of marriage contracts through teleconference technology or other online media, while the development of information technology is faster and faster when compared to development of legal substance. The issue of the marriage contract via teleconference caused controversy because of differences in interpretation of the concept of the unity of the assembly. This research is a type of normative legal research. Normative legal research that focuses on legal principles related to the implementation of the marriage contract. This study is descriptive in nature, collecting information about a teleconference marriage contract phenomenon. The approach used is a normative theological approach, phenomenology and philosophy. The analytical knife uses the maqashid shariah theory in observing the marriage contract by teleconference. The research findings show that the marriage contract through teleconference which was carried out during the Covid-19 pandemic was reviewed according to maqashid shariah is a legal event that is allowed, and this will be an alternative to avoid harm as a goal to maintain the human soul.